Economic policy coordination in the Economic and Monetary Union: from Maastricht via the SGP to the fiscal pact - Mortensen, Jorgen (Brussels, 2013)
"This paper first takes a step backwards with an attempt to situate the recent adoption of the Treaty on Stability, Coordination and Governance in the Economic and Monetary Union in the context of discussions on the Stability and Growth Pact (SGP) and the ‘Maastricht criteria’, as fixed in the Maastricht Treaty for membership in the Economic and Monetary Union (EMU) in a longer perspective of the sharing of competences for macroeconomic policy-making within the EU. It then presents the main features of the new so-called ‘Fiscal Compact’ and its relationship to the SGP and draws some conclusions as regards the importance and relevance of this new step in the process of economic policy coordination. It concludes that the Treaty on Stability, Coordination and Governance in the Economic and Monetary Union does not seem to offer a definitive solution to the problem of finding the appropriate budgetary-monetary policy mix in EMU, which was already well identified in the Delors report in 1989 and regularly emphasised ever since and is now seriously aggravated due to the crisis in the eurozone. Furthermore, implementation of this Treaty may under certain circumstances contribute to an increase in the uncertainties as regards the distribution of the competences between the European Parliament and national parliaments and between the former and the Commission and the Council."